1985
DOI: 10.1088/0031-8949/32/1/006
|View full text |Cite
|
Sign up to set email alerts
|

Surface Core Level Shifts of the Lanthanide Metals Ce58-Lu71: A Comprehensive Experimental Study

Abstract: Synchrotron radiation excited photoelectron spectra of the 4f emission region for all lanthanide metals Cess to Lu" (except Pm6') have been recorded. Photon energies ranging from 30 eV to 200 eV have been used to excite the 4f electrons with maximum surface sensitivity. The 4f emission spectra of all metals studied, with the exception of Ce, show 4f emission from the surface layer atoms and the bulk atoms as clearly separated structures with different binding energies. For Ce no unambiguous separation of the 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(31 citation statements)
references
References 38 publications
3
27
0
1
Order By: Relevance
“…Таким образом, поверхностный сдвиг 4 f -уровня для нанопленки иттербия толщиной 16 ML, нанесенной на Si(111) подложку, составляет 0.58 eV. Эта величина хорошо согласуется с данными, полученными для трехмерных образцов иттербия (см., например, [9]). …”
Section: результаты и их обсуждениеunclassified
“…Таким образом, поверхностный сдвиг 4 f -уровня для нанопленки иттербия толщиной 16 ML, нанесенной на Si(111) подложку, составляет 0.58 eV. Эта величина хорошо согласуется с данными, полученными для трехмерных образцов иттербия (см., например, [9]). …”
Section: результаты и их обсуждениеunclassified
“…There are broad peaks in the theoretical conductivity around 3.0 eV in both GdFe2 Energy (eW unoccupied 4f levels of bulk Gd metal are -8.5 and 3.5 eV with respect to the Fermi level, respectively, from PES and'IPES data [123]. The LSDA calculations for GdFez by the LMTO method by Hiroshi [124] give the locations of the occupied and unoccupied…”
Section: 43mentioning
confidence: 99%
“…Photoemission experiments have shown that the surface atoms might have a different 4f configuration than the bulk atoms [Allen 1980, Wertheim 1978, Lang 1979. Figure 1.5 [Gerken 1985] shows the Sm valence spectrum obtained at three different photon energies. Multiple peaks observed in the spectrum can be grouped into two subsets, one from the bulk emission (4f5 to 4f4), and the other from the surface emission (4f6 to 4f5).…”
Section: Valence Induced Phase Transitionmentioning
confidence: 99%
“…Comparison between an XPS-spectrum and two spectra recorded at 35 eV and 100 eV photon energy of the 4f emission region of Sm. Also shown are the multiplet intensities for the bulk emission (4f5 to 4f^), the surface emission (4f^ to 4f5) and the buUc BIS transition (4f5 to 4f6) (after [Gerken 1985]). …”
Section: Valence Induced Phase Transitionmentioning
confidence: 99%
See 1 more Smart Citation